Is Titanium Sensitivity Associated with Allergic Reactions in Patients with Dental Implants? A Systematic Review. (17th March 2011) - Javed, Fawad; Al‐Hezaimi, Khalid; Almas, Khalid; Romanos, George E.
ABSTRACT Background: A worrying correlation which seems to be overlooked by clinicians is allergic reactions to titanium (Ti) in patients with dental implants. Purpose: The aim of the present review study was to assess whether or not Ti sensitivity is associated with allergic reactions in patients with dental implants. Materials and Methods: To address the focused question "Can Ti cause allergic reactions in patients with dental implants?", databases were explored from 1977 until May 2010 using a combination of the following keywords: "allergy, ""dental, ""hypersensitivity, ""implant, ""oral, " and "Titanium." Letters to the editor and unpublished data were excluded. Results: Seven studies (six clinical and one experimental) were included. The participants were aged between 14.3 and 84.1 years. In five clinical studies, Ti implants were inserted in the mandible. Five studies reported dermal inflammatory conditions and gingival hyperplasia as allergic reactions in patients with Ti dental implants. A case report presented swelling in submental and labial sulcus and hyperemia of soft tissues in a patient with Ti dental implants. Two studies reported that Ti implants are well tolerated in host tissues. The patch test was performed in two clinical studies for the diagnosis of allergic reactions. Memory lymphocyte immunostimulation assay and lymphocyte transformation tests were also performed. Conclusion: The significance of Ti as a cause of allergic reactions in patients with dental implants remains unproven.